Dampak Interaksi Di Media Sosial: Berubahkah Penerimaan Diri Generasi Digital? - Gisella Arnis Grafiyana; Eka Rizki Meilani; Nia Anggri Noveni; Dion Romodhon (Psychopolytan : Jurnal Psikologi, 2025)
The impact of digitalization has made many changes, one of which is the shift in face-to-face communication patterns which have now become less popular interactions. This often gives rise to new problems, especially in self-acceptance which is depicted through the body image of teenagers who portray themselves on social media, the internet generation or often known as generation Z. The aim of this research is to get a picture of Generation Z's self-acceptance in terms of body image and self-disclosure on social media. This research method uses quantitative with mediation analysis using the SEM-PLS application. There were 168 subjects in this research aged 18-21 years. The research results show that self-disclosure can be predicted (R2=0.229) by self-acceptance and body image, it also proven that body image (f2=0.178) can more explain the change of self-acceptance than self-disclosure (f2=0.109). From these results it can be concluded that body image has positif effect for individual self-acceptance, while this is related to self-acceptance which is more influenced by internal factors rather than how the individual express to other such as self-disclosure.